The (im)possibility to forgive - some aspects of forgiveness and ressentiment - Todorovska, Marija (Православен богословски факултет, Скопје, 2018)
The paper offers an overview of the (im)possibility to forgive in Vladimir Jankélévitch and Jacques Derrida, and quite briefly tackles some of the criticisms of John Milbank, as well as some aspects of ressentiment in Jean Améry. Jankélévitch’s conception of pure forgiveness as an instantaneous, inter-personal, gratuitous, gracious gift, ineffable and beyond the established systems in comparison to pseudo-forms of forgiveness is shown, along with his divergence from the idea that Evil is forgivable, towards his insistence that some instances of supreme evil abolish the possibility for forgiveness. Derrida’s distinction between true forgiveness and reconciliation for the sake of healing is tackled, with his ideas of forgiveness as beyond the range of justice, and possible because of being impossible (as only the unforgivable is forgivable). Milbank’s ideas on negative and positive forgiveness are related to his emphasis on the importance of the collective good of a value-sharing community, and Améry’s stance on the impossibility to forgive as a result of profound, ever-lasting trauma is mentioned.